Diagnostic criteria for atypical hemolytic uremic syndrome proposed by the Joint Committee of the Japanese Society of Nephrology and the Japan Pediatric Society. Issue 1 (February 2014) - Sawai, Toshihiro; Nangaku, Masaomi; Ashida, Akira; Fujimaru, Rika; Hataya, Hiroshi; Hidaka, Yoshihiko; Kaname, Shinya; Okada, Hirokazu; Sato, Waichi; Yasuda, Takashi; Yoshida, Yoko; Fujimura, Yoshihiro; et al.
Abstract Atypical hemolytic uremic syndrome (aHUS) is rare and comprises the triad of microangiopathic hemolytic anemia, thrombocytopenia, and acute kidney injury. Recently, abnormalities in the mechanisms underlying complement regulation have been focused upon as causes of aHUS. The prognosis for patients who present with aHUS is very poor, with the first aHUS attack being associated with a mortality rate of approximately 25%, and with approximately 50% of cases resulting in end‐stage renal disease requiring dialysis. If treatment is delayed, there is a high risk of this syndrome progressing to renal failure. Therefore, we have developed diagnostic criteria for aHUS to enable its early diagnosis and to facilitate the timely initiation of appropriate treatment. We hope these diagnostic criteria will be disseminated to as many clinicians as possible and that they will be used widely.